Engineered cell‐to‐cell signalling within growing bacterial cellulose pellicles. Issue 4 (21st November 2018) - Walker, Kenneth T.; Goosens, Vivianne J.; Das, Akashaditya; Graham, Alicia E.; Ellis, Tom
Summary: Bacterial cellulose is a strong and flexible biomaterial produced at high yields by Acetobacter species and has applications in health care, biotechnology and electronics. Naturally, bacterial cellulose grows as a large unstructured polymer network around the bacteria that produce it, and tools to enable these bacteria to respond to different locations are required to grow more complex structured materials. Here, we introduce engineered cell‐to‐cell communication into a bacterial cellulose‐producing strain of Komagataeibacter rhaeticus to enable different cells to detect their proximity within growing material and trigger differential gene expression in response. Using synthetic biology tools, we engineer Sender and Receiver strains of K. rhaeticus to produce and respond to the diffusible signalling molecule, acyl‐homoserine lactone. We demonstrate that communication can occur both within and between growing pellicles and use this in a boundary detection experiment, where spliced and joined pellicles sense and reveal their original boundary. This work sets the basis for synthetic cell‐to‐cell communication within bacterial cellulose and is an important step forward for pattern formation within engineered living materials. Abstract : A synthetic quorum sensing system is engineered to work in bacterial cellulose producing bacteria. This enables cells to be programmed to sense and respond to one another within the growing cellulose material.